2017
DOI: 10.1063/1.4979501
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric energy harvester for low engine vibrations

Abstract: Piezoelectric materials are well known for their use as sensors and actuators in flexible structures. Researchers have also focused on harvesting energy from the waste vibrations generated by different sources using piezoelectric materials. In its running condition, an engine generates vibrations. These vibrations can be converted into electric energy by using a suitable energy harvester. The minute energy generated from these waste vibrations can be used as an additional source to batteries or a resource to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…A variety of energy-harvesting methods have been proposed for different applications in the automotive industry. 110,[228][229][230][231][232][233][234] Here our analysis concentrates on energy harvesters for the TPMS. Tires are the only components in vehicles that directly contact the ground.…”
Section: Tire Pressure Monitoring Systemmentioning
confidence: 99%
“…A variety of energy-harvesting methods have been proposed for different applications in the automotive industry. 110,[228][229][230][231][232][233][234] Here our analysis concentrates on energy harvesters for the TPMS. Tires are the only components in vehicles that directly contact the ground.…”
Section: Tire Pressure Monitoring Systemmentioning
confidence: 99%
“…Vibration harvesting from engine vibrations was demonstrated with a cantilever harvester with 155 mm length that was installed on the vehicle engine and tested in various engine speeds. [61] The system is shown in Figure 7a. It is found that in frequency match condition of around 2000 rpm engine speed, more energy can be harvested.…”
Section: Engine Vibrationsmentioning
confidence: 99%
“…Reproduced with permission. [61] Copyright 2017, AIP Publishing LLC. b) Self-powered wireless sensor system.…”
Section: Gait Power For Personal Health Carementioning
confidence: 99%
“…Khalatkar et al (2011) presented a finite element method (FEM)-based model and simulation to determine the optimum place for mounting the PZT patch on the cantilever-type beam energy harvester. Khalatkar and Gupta (2017) designed and developed a piezoelectric energy harvester to harvest energy from engine vibrations at low frequencies. Rezaei-Hosseinabadi et al (2015) developed a piezoelectric beam harvester, coupled with a wind turbine.…”
Section: Introductionmentioning
confidence: 99%